The impact of glucose metabolism on inflammatory processes in sepsis-induced acute lung injury - Cheng, Shilei; Li, Yufei; Sun, Xiaoliang; Liu, Zhirui; Guo, Liang; Wu, Jueheng; Yang, Xiaohan; Wei, Sisi; Wu, Guanghan; Xu, Shilong; Yang, Fan; Wu, Jianbo (Frontiers in Immunology, 2024)
Acute lung injury (ALI) is a prevalent and critical complication of sepsis, marked by high incidence and mortality rates, with its pathogenesis still not being fully elucidated. Recent research has revealed a significant correlation between the metabolic reprogramming of glucose and sepsis-associated ALI (S-ALI). Throughout the course of S-ALI, immune cells, including macrophages and dendritic cells, undergo metabolic shifts to accommodate the intricate demands of immune function that emerge as sepsis advances. Indeed, glucose metabolic reprogramming in S-ALI serves as a double-edged sword, fueling inflammatory immune responses in the initial stages and subsequently initiating anti-inflammatory responses as the disease evolves. In this review, we delineate the current research progress concerning the pathogenic mechanisms linked to glucose metabolic reprogramming in S-ALI, with a focus on the pertinent immune cells implicated. We encapsulate the impact of glucose metabolic reprogramming on the onset, progression, and prognosis of S-ALI. Ultimately, by examining key regulatory factors within metabolic intermediates and enzymes, We have identified potential therapeutic targets linked to metabolic reprogramming, striving to tackle the inherent challenges in diagnosing and treating Severe Acute Lung Injury (S-ALI) with greater efficacy.